‘Mountain resorts’: origins and evolution - Kowalczyk, Andrzej (Turyzm/Tourism, 2009)
The paper discusses the background for the emergence of such ‘mountain resorts’, their types and changes in their mode of operation. Some theoretical and practical issues will be illustrated with examples derived from Europe, North America, Asia and Africa.